Assessment of chemical, microbiological and sensory quality of Sous vide cooked Luciobarbus esocinus (Heckel, 1843) during chilled storage - Gürel İnanli, Ayşe; Yaz, Yelda (Progress in Nutrition, 2020)
The aim of this study was to investigate chemical, microbiological and sensory quality of sous-videcooked Luciobarbus esocinus (Heckel, 1843) during chilled storage. Moisture, ash, fat, protein, salt, pH, totalvolatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARs), counts of aerobic mesophilebacteria, aerobic psychrophile bacteria and yeast-mold were determined in the raw material. The sensorial,chemical and microbiological changes of products obtained under the cold storage were analyzed in 3 daysinterval with three replicates. TermsTVB-N value in group C was determined as 11.06 mg/100 g, in the S1group as 10.40 mg/100 g, and in the S2 group as 11.99 40 mg / 100 g (p